2020
DOI: 10.1186/s12199-020-00886-1
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of hematological parameters of petrol filling workers at petrol stations in Gondar town, Northwest Ethiopia: a comparative cross-sectional study

Abstract: Background: Petrol is the non-specific term for petroleum which is used for inside combustion of engines. Petrol filling workers are highly vulnerable to occupational exposure to these harmful substances which lead to hematotoxicity and blood disorders such as leukemia, aplastic anemia, and dysplastic bone marrow. Thus, this study was aimed to assess hematological parameters of petrol filling workers in Gondar town, Northwest Ethiopia. Methods: A comparative cross-sectional study was conducted from January to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Despite the higher rate of monocytes found in total of workers, a lower rate of monocytes was associated with a high number of CAs (group two), highlighting the importance of the simple classic blood test in monitoring their overall health. Recently, Getu et al ( 2020 ) studied GSW in Ethiopia. In disagreement to our study, they found that hematimetric values had a significant increment when compared with the control group.…”
Section: Risk Behavior and Prevention Of Cancermentioning
confidence: 99%
“…Despite the higher rate of monocytes found in total of workers, a lower rate of monocytes was associated with a high number of CAs (group two), highlighting the importance of the simple classic blood test in monitoring their overall health. Recently, Getu et al ( 2020 ) studied GSW in Ethiopia. In disagreement to our study, they found that hematimetric values had a significant increment when compared with the control group.…”
Section: Risk Behavior and Prevention Of Cancermentioning
confidence: 99%
“…When job demands overload the abilities and coping skills of workers, they become a risk factor, generating stress and other health problems [15]. Workers must fulfil certain job demands and complete repetitive and mundane daily tasks in a fast-paced and dangerous work environment [16,17], which often lead to high-workload fatigue and job burnout.…”
Section: Job Characteristics Of Gas Station Workersmentioning
confidence: 99%
“…Protective equipment such as masks, gloves, goggles, and uniforms are required to reduce the intensity of exposure and prevent occupational exposure [34]. This can easily lead to workplace accidents and health problems if workers are regularly exposed to organic solvents without adequate protection [17]. Workers may experience anxiety and insecurity as a result of their low job security, which lead to negative emotions and affect their well-being.…”
Section: Chemical and Physical Risks In The Workplacementioning
confidence: 99%
“…Regular blood tests are already in use for BTEX-exposed workers, as even low levels of benzene exposure may lead to white blood cells (lymphocyte and B cells) as well as granulocyte suppression [11] . Such abnormalities in the blood of gas station workers in Gondar town, Northwest Ethiopia [12] have been reported.…”
Section: Surveillance Biomarkersmentioning
confidence: 99%